2003
DOI: 10.1097/01.ju.0000035910.75480.4b
|View full text |Cite
|
Sign up to set email alerts
|

Port Site Metastases in Urological Laparoscopic Surgery

Abstract: Port site metastases is a multifactorial phenomenon with an as yet undetermined incidence. The problem is influenced to some extent by surgeon and operating team experience and, therefore, it could be partially prevented. The suggested preventive steps are avoiding laparoscopic surgery when there are ascites, trocar fixation to prevent dislodgment, avoiding gas leakage along and around the trocar, sufficient technical readiness of the operating team (adequate laparoscopic equipment and technique, minimal handl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 65 publications
1
70
0
2
Order By: Relevance
“…Measures suggested in the Literature to prevent Urologic Port-site Metastasis 31 • Avoidance of laparoscopic surgery if ascites is present 9,31 • Avoidance of gas leakage along the trocar 31 • Avoidance of tumor-boundary violation…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures suggested in the Literature to prevent Urologic Port-site Metastasis 31 • Avoidance of laparoscopic surgery if ascites is present 9,31 • Avoidance of gas leakage along the trocar 31 • Avoidance of tumor-boundary violation…”
Section: Discussionmentioning
confidence: 99%
“…2 Laparoscopic surgery has equivalent oncologic outcomes to open procedures; however, PSM is rare, troubling, and often an unexplained occurrence. The first known occurrence of PSM after a urologic procedure was in 1994, when Stolla et al 9 reported a case of subcutaneous metastasis of bladder transitional cell carcinoma (TCC) after laparoscopic pelvic lymph node dissection. Since then, about 50 PSMs have been reported in the setting of urologic surgery.…”
Section: In 1978 the Authors Reported Implantation Ofmentioning
confidence: 99%
“…28,30,34,35 Additionally, Kebebew et al demonstrated that inadvertent laparoscopic resection of clinically unsuspected adrenocortical carcinoma exhibited a high local recurrence rate. 19 Gerber et al reported on their experience with laparoscopic adrenalectomy for lung cancer patients with a solitary metastasis to the adrenal gland.…”
Section: Surgical Management Of Adrenal Metastasismentioning
confidence: 99%
“…35 Causes of port site metastasis can be grouped into several categories: tumor aggressiveness (type of tumor and its natural behavior), local wound factors (implanting in the early stages of wound healing, tumor cell adherence to wound margins, and release of growth factors), host immune response, and laparoscopy-related factors (ie, type of gas used for insufflation, surgical manipulation, tumor spillage). 35 In their review of the urologic literature, Tsvian et al found nine cases of port site metastasis. The putative causative factors of port site metastasis were high stage or grade primary tumor, violation of tumor boundaries, intracorporeal morcellation of the tumor specimen, and disuse of an entrapment bag during specimen retrieval.…”
Section: Surgical Management Of Adrenal Metastasismentioning
confidence: 99%
See 1 more Smart Citation